A psychobiographical study of Antwone Fisher - Wannenburg, Nicola (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Psychobiographical researchers methodically formulate life histories and interpret them by means of psychological theories. The research typically focuses on exemplary and completed lives. The cases that are studied are usually of individuals who are of particular interest to society as a result of excelling in their particular fields, be they to society's benefit or detriment. Antwone Fisher was chosen for this study using purposive sampling as he meets the psychobiographical requirement of being an extraordinary individual. Fisher grew up in the Foster Care System and faced many abusive experiences as child. Despite difficult beginnings, Fisher developed into a stable and creative adult who excels as a poet, screenwriter and film director. The primary aim of this study is to describe and interpret the life of Antwone Fisher through Erikson's theory of psychosocial development. The data was processed and analysed using Miles and Hubermans' general view of qualitative analyses as well as Alexander's method of asking the data questions. This study contributes to the development of psychobiographical research in South Africa as well as to personality and developmental theory.
Keywords: Fisher, Antwone Quenton; Psychology -- Biographical methods; Psychoanalysis; Abused children -- Biography